Centrifuge modelling of the ground reaction curve in fibre-reinforced soil - Cox, Craig Mark (2014)
The phenomenon known as the ‘arching effect’ occurs when a portion of granular mass yields relative to an adjacent stationary region. The movement is resisted by shearing stresses which act to reduce the pressure on the yielding support and increase the pressure on the adjacent stationary supporting zones. Arching is widely observed in both natural and man-made structures such as piled embankments, tunnelling, and above mine works and sinkholes.